Citrate-buffered Yamanaka medium allows to produce high-yield bacterial nanocellulose in static culture using Komagataeibacter strains isolated from apple cider vinegar - Núñez, Dariela; Oyarzún, Patricio; Cáceres, Rodrigo; Elgueta, Elizabeth; Gamboa, Maribet (Frontiers in Bioengineering and Biotechnology, 2024)
Bacterial nanocellulose (BNC) is a sustainable, renewable, and eco-friendly nanomaterial, which has gained great attentions in both academic and industrial fields. Two bacterial nanocellulose-producing strains (CVV and CVN) were isolated from apple vinegar sources, presenting high 16S rRNA gene sequence similarities (96%–98%) with Komagataeibacter species. The biofilm was characterized by scanning electron microscopy (SEM), revealing the presence of rod-shaped bacteria intricately embedded in the polymeric matrix composed of nanofibers of bacterial nanocellulose. FTIR spectrum and XRD pattern additionally confirmed the characteristic chemical structure associated with this material. The yields and productivities achieved during 10 days of fermentation were compared with Komagataeibacter xylinus ATCC 53524, resulting in low levels of BNC production. However, a remarkable increase in the BNC yield was achieved for CVV (690% increase) and CVN (750% increase) strains at day 6 of the fermentation upon adding 22 mM citrate buffer into the medium. This effect is mainly attributed to the buffering capacity of the modified Yakamana medium, which allowed to maintain pH close to 4.0 until day 6, though in combination with additional factors including stimulation of the gluconeogenesis pathway and citrate assimilation as a carbon source. In addition, the productivities determined for both isolated strains (0.850 and 0.917 g L−1 d−1) compare favorably to previous works, supporting current efforts to improve fermentation performance in static cultures and the feasibility of scaling-up BNC production in these systems.